Discussing Inclusive Agroecological Innovations with Farmers in the Tunisian Agroecological Living Landscape (ALL) for Sustainable Crop Livestock Farming Systems - Idoudi, Zied (International Center for Agricultural Research in the Dry Areas, 2022)
Discussing Inclusive Agroecological Innovations with Farmers in the Tunisian Agroecological Living Landscape (ALL) for Sustainable Crop Livestock Farming Systems.